Connecting personality traits to social networking site addiction: the mediating role of motives. Issue 2 (4th October 2019) - Chen, Adela; Roberts, Nicholas
Abstract : Purpose: The purpose of this paper is to investigate whether four motives – conformity, enhancement, social and coping – mediate relationships between four personality types – agreeableness, extraversion, neuroticism and openness to experience – and social networking site (SNS) addiction. Impulse control is included as a moderator. Design/methodology/approach: The paper uses a survey to collect data at two points in time from 304 SNS users. Structural equation modeling was used for data analysis. Findings: Empirical results show that conformity, enhancement and coping motives act as mediators between various personality types and SNS addiction. Furthermore, impulse control weakens the effects of two motives – enhancement and social – on SNS addiction. Research limitations/implications: The research model included only four motives. Future research could investigate other motivational mechanisms and moderators. The research method surveyed university students in the USA; thus, results may not generalize to a different user population. The method also included only one SNS, Facebook. Originality/value: The paper contributes to the literature by showing that motives of SNS use connect personality to SNS addiction. This study also shows that self-reflective factors like impulse control can reduce the positive effects of motives on SNS addiction.